2019
DOI: 10.1038/s41598-018-37615-2
|View full text |Cite
|
Sign up to set email alerts
|

Mass Effect Deformation Heterogeneity (MEDH) on Gadolinium-contrast T1-weighted MRI is associated with decreased survival in patients with right cerebral hemisphere Glioblastoma: A feasibility study

Abstract: Subtle tissue deformations caused by mass-effect in Glioblastoma (GBM) are often not visually evident, and may cause neurological deficits, impacting survival. Radiomic features provide sub-visual quantitative measures to uncover disease characteristics. We present a new radiomic feature to capture mass effect-induced deformations in the brain on Gadolinium-contrast (Gd-C) T1w-MRI, and their impact on survival. Our rationale is that larger variations in deformation within functionally eloquent areas of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…45 Deformation descriptors are another class of functional radiomics markers which seek to measure tissue deformation in the brain parenchyma due to mass effect. 46 These features provide an insight into the microenvironment outside the visible surgical margins.…”
Section: Radiomic Feature Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…45 Deformation descriptors are another class of functional radiomics markers which seek to measure tissue deformation in the brain parenchyma due to mass effect. 46 These features provide an insight into the microenvironment outside the visible surgical margins.…”
Section: Radiomic Feature Groupsmentioning
confidence: 99%
“…Prasanna et al 46 discussed how mass effect-induced deformation heterogeneity (MEDH) from glioblastoma on multi-sequence MRI affects survival. High expression of MEDH in the areas of language comprehension, social cognition, visual perception, emotion, somatosensory, cognitive and motor-control functions were found to be associated with worse survival (Fig.…”
Section: Prognostic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dMRI was fitted with a tensor model to produce an FA map using the FSL diffusion toolbox (FDT) 44 . The FA maps were then nonlinearly co-registered to the MNI-152 space FA template using the deformable function of ANTs, which is shown to outperform the default deformable registration tools FNIRT 45 of TBSS in the co-registration of FA 46 and pathology-bearing T1 images 47 , and more importantly, could mitigate the deformation of the brain with tumor, by accounting for the tumor mass effect 48 . To minimize the bias of the signal-noise ratio introduced by the different MRI acquisition protocols, we normalized the FA map using the MRI intensity histogram-matching method 49 .…”
Section: Methodsmentioning
confidence: 99%
“…The per-voxel deformation measurements from the BAT region are then used as radiomic features for analysis. Prasanna et al 70 hypothesized that larger variations in deformation within functional areas of the contralateral hemisphere are likely related to decreased survival in GBMs. They demonstrated that decreased OS was found to be associated with increased deformation in areas of language comprehension, visual perception, cognitive, and motor-control functions, particularly in the memory areas in the left hemisphere.…”
Section: Overview Of Radiomic and Radiogenomics Pipelinementioning
confidence: 99%